Effects of appointing new independent directors who are professionally affiliated with their predecessors: Evidence from China. (5th May 2022) - Li, Yanlin; Tian, Gary Gang; Wang, Xin
Abstract: The roles played by independent directors (IDs) have been extensively documented, but the question of how they are appointed remains insufficiently explored. We found that the likelihood of IDs being appointed was higher when they were professionally affiliated with the departing IDs, and this effect was more pronounced when either the predecessor had a compliant voting record or held more directorships in other firms controlled by insiders in the focal firm. The appointment of affiliated IDs who colluded with insiders through predecessors is positively associated with fewer dissenting votes, more related‐party transactions, and more severe violations. The effect was stronger for firms that had higher concentrated ownership and were located in areas with a weak institutional environment. Our research showed that predecessors with low independence helps establish a reciprocity norm between affiliated successors and insiders, leading to weak board monitoring.